Pattern of prescribing at a paediatric outpatient setting in northern India - T, Pramil; A, Rajiv; G, Gaurav (Indian Journal of Pharmacy Practice)
Introduction Drug prescribing is a skill that needs to be refined on a continuing basis. It reflects physician's skills and attitude toward diagnosis of an ailment and selection of appropriate treatment. In view of this, it is important to do study the pattern of prescribing in paediatric patients on continuous basis. The aim of this study was to analyze the prescribing pattern in a paediatric outpatient setting. Methods: A drug utilization study was carried out in a paediatric outpatient setting in northern India for period of 4 months, on a pilot basis. The study is continuing. The prescriptions of children up to 18 years approaching the clinic were studied and the data was captured from the “Wisekid” software. The data was analysed to determine WHO recommended prescribing indicators and three complementary indicators for cost. Results: The data were collected from 436 prescriptions and it was found that upper respiratory tract illness is the most common illness (31%). The average number of drugs prescribed was 3.2±0.06, while drugs prescribed by generic name were 3.8%. Percentage of encounter with injection and antimicrobials prescribed were found to be 0.9% and 18% respectively. The prescribing from National List of Essential Medicine (NLEM-2011) was found to be 39.6%. The median cost of drug per encounter was INR132, while cost spent on injection and antimicrobials were 0.3% and 7%, respectively. Conclusion: The prescribing pattern in private paediatric outpatient setting were found to be rational as less number of antimicrobial drugs and injections were use in the practice. A very fair number of medicines were prescribed from the National List of Essential medicine (NLEM-2011).
Keywords: Prescribing pattern; Drug utilization; Pediatrics; Out-patients; India